2002
DOI: 10.1177/106648002236758
|View full text |Cite
|
Sign up to set email alerts
|

Long-Distance Relationships in Dual-Career Commuter Couples: A Review of Counseling Issues

Abstract: The dual-career commuter couple is an alternative family configuration that continues to grow in number. This article is a review of the literature on dual-career commuter couples that has been published since the Gerstel and Gross review in 1982. It addresses the counseling issues of marital and family characteristics, commuting characteristics, and decision-making styles. Counseling implications and future research needs are also included. This updated information is important to counselors who are trying to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
14

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 12 publications
0
30
0
14
Order By: Relevance
“…They need to know how variables (e.g., MBs) may function in unique and similar ways in LDRs and GCRs. For instance, counselors with LDR clients may explicitly discuss stress management (Rhodes, 2002). Given the present results, counselors can coach LDR clients to think about MBs and RCCUs.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…They need to know how variables (e.g., MBs) may function in unique and similar ways in LDRs and GCRs. For instance, counselors with LDR clients may explicitly discuss stress management (Rhodes, 2002). Given the present results, counselors can coach LDR clients to think about MBs and RCCUs.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Indeed, there are other occupations that have long been associated with marital separation, for example military personnel, salesman, airline pilots and long-distance lorry drivers. Studies using such samples have focused on commuter/dual-career relationships or long-distance relationships (Blake, 1996;Harris et al, 2002;O'Dorisio & O'Dorisio, 2003;Rhodes, 2002;Morris, 1995;Schneider & Waite, 2005;Tessina, 2008), where couples see each other on weekends. Couples who choose to live separately; a term coined 'Living Apart…”
Section: Existing Literature On Business Travelmentioning
confidence: 99%
“…Similarly, Rosen (1991) identified that 83% of women and 72% of men experienced significant levels of conflict between work and family roles. The greater proportion of women reporting work and family conflict has been attributed to the rapid increase of married women entering the work force (Noor, 2002;Rhodes, 2002), while continuing to maintain the majority of the family and household responsibilities (Jackson, Tal, & Sullivan, 2003;Kaltreider, 1997). Within the last decade men have assumed more family responsibilities, in part due to high rates of divorce resulting in increased involvement in single parenting (Kinnunen, Gerris, & Vermulst, 1996;Kinnunen & Mauno, 1998).…”
Section: Introductionmentioning
confidence: 97%